Nusyuz Isteri Tidak Menggugurkan Nafkah Menurut Ibnu Hazm dan Relevansinya dengan Hukum Keluarga Indonesia - Jumni Nelli; Isra Yuliana (AL-FIKRA, 2022)
Setting the rules for not being given a living by a nusyuz wife causes a discussion in the study of fiqh. This is considered by contemporary scholars as an act of discrimination against women, if it is associated with the application of joint property in Indonesian Islamic family law, it will cause ambiguity. In contrast to Ibn Hazm, he is of the opinion that a nusyuz wife does not lose her livelihood. This study is to answer Ibn Hazm's reasons for establishing a living for a nusyuz wife, as well as its relevance to Islamic family law in Indonesia. This research is a library research by tracing classic books and other supporting books, using content analysis (content analysis). The results of this study state that Ibn Hazm said that a nusyuz wife is still obligated to be supported. Ibn Hazm postulated with zhahir verses of the Qur'an letter al-Nisa' verse 34 and the hadith of the Prophet SAW because there is no textual mention of the loss of livelihood for a nusyuz wife. Ibn Hazm's opinion is relevant to be used for Indonesian Islamic family law, because joint property applies.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//